OPTIMIZING THE INFORMATION QUALITY OF FINANCIAL STATEMENT AND GOOD GOVERNMENT GOVERNANCE THROUGH INTERNAL CONTROL SYSTEM AND HUMAN RESOURCE COMPETENCE - Dewi, Nur Fitri (Universitas Dian Nuswantoro, 2023)
The purpose of this paper is to determine the influence of the internal control system and human resource competence on good government governance and its influence on the information quality of financial statements. The data collection method was a questionnaire distributed to 65 samples of the Regional Financial and Asset Management Agency (BPKAD) of South Sumatra Province. The collected data was processed using SPSS 27.00 with t-test and Path Analysis. The research results show that the internal control system and human resource competence have a positive effect on good government governance. The internal control system and human resource competence also have a positive influence on the information quality of financial statements, both directly and indirectly, mediated by good government governance. Apart from that, good government governance has a direct and positive effect on the information quality of financial statements. The results of this research can be helpful for the government as input and consideration in determining policies, especially regarding improving good government governance and the quality of information on government financial statements.Keywords: Internal Control System; Human Resource Competence; Good Government Governance; The Information Quality of Financial Statement